The interleukin-7 receptor alpha chain transmits distinct signals for proliferation and differentiation during B lymphopoiesis. - Corcoran, A E (1996)
The interleukin 7 receptor (IL7R), which contains a unique alpha chain and a gamma chain shared by other cytokine receptors, is indispensable for normal lymphocyte development. The basis for this role is poorly understood. Here we show that the IL7R alpha chain not only causes progenitors to proliferate, but also has a distinct activity in inducing differentiation. First, we identify a single cytoplasmic tyrosine residue in the IL7R alpha chain that is essential for cell cycle entry and proliferation dependent on phosphatidylinositol 3-kinase. We use a mutant alpha chain in which this residue has been altered to reconstitute B lymphopoiesis by retrovirus-mediated gene transfer in cultures of bone marrow from mice deficient in IL7R alpha chain. The mutation abrogates the proliferation of B-lymphocyte progenitors, but reveals a novel function of the alpha chain in promoting immunoglobulin heavy chain gene rearrangement leading to B-cell differentiation. This function is lost (but proliferation sustained) when the cytoplasmic domain of IL7R alpha is replaced by corresponding sequences from the IL2R, despite the similarity on their signalling mechanisms. Thus, the signals which mediate a differentiative function of the IL7R in B lymphopoiesis are specific and distinct from those causing proliferation.